Isolation, Characterization, and Antioxidant Activity of Phosvitin from Duck Egg Yolk - Muhammad Hipzul Mursyid; Sulaiman N. Depamede; Made Sriasih (Postgraduate, University of Mataram, 2026)
Phosvitin is a highly phosphorylated protein found in egg yolk and is known for its strong metal-binding capacity and antioxidant activity. This study aimed to isolate and characterize phosvitin from duck egg yolk (Anas platyrhynchos domesticus) and evaluate its antioxidant potential. Phosvitin was isolated using a modified extraction method and characterized using one-dimensional gel electrophoresis (SDS-PAGE) and Fourier Transform Infrared (FTIR) spectroscopy. Antioxidant activity was determined using the DPPH radical scavenging assay. The results showed that phosvitin was successfully isolated, indicated by a dominant protein band at approximately 50 kDa. The antioxidant activity exhibited a strong inhibitory effect with an IC50 value of 33.65 ppm, indicating very strong antioxidant activity. FTIR analysis confirmed the presence of characteristic functional groups, including amide and phosphate groups, which are typical of phosphoproteins. These findings suggest that phosvitin from duck egg yolk may be a promising natural antioxidant for food and pharmaceutical applications.